Effective inhaler technique education is achievable - assessment and comparison of five inhaler devices errors - Marko, Monika; Klimczak, Magdalena; Sobczak, Marharyta; Wojakiewicz, Maciej; Dębowski, Tomasz; Emeryk, Andrzej; Pawliczak, Rafał (Frontiers in Pharmacology, 2025)
ObjectiveThe study is based on a respiratory educational program aimed at training medical personnel to use inhalers correctly and educating patients on improving their inhalation skills.MethodsAdult patients with asthma were divided into groups according to the inhaler: Ellipta, Diskus, Cyclohaler, Pressurized metered-dose inhaler (pMDI), and Turbuhaler. Patients were assessed for inhalation skills and then educated by previously trained nurses. The results were collected in forms allowing the evaluation of the number of critical and other errors made by patients.ResultsThe number of errors during inhalers use decreased at subsequent visits after education. The number of critical errors was lower than other errors for each device before and after education. Statistically significant differences in the inhalation technique assessment (before education, visit 1, and visit 2) were shown for Cyclohaler and pMDI (p < 0.0001), Turbuhaler (p = 0.0014), Diskus (p = 0.0025) and Ellipta (p = 0.0091).ConclusionBefore education, the least technical difficulties were observed for the Cyclohaler, while in the Ellipta group, patients made the most errors. Education resulted in equalizing the level of correctness of inhalation, which was similarly high for each type of device. This means that after education, all inhalers have similar difficulty levels in performing the correct inhalation technique. However, achieved improvement may be influenced by other factors such as practice effects or confounding variables due to real-life nature of the study.